SPIRITUAL INTELLIGENCE MANAGEMENT ACCORDING TO HADROTUS SYAIKH KH HASYIM ASY'ARI:: A Study of The Book Adabul Alim wa Muta'alim - Lutfi, Muhammad Fatah; Sopingi, Imam; Hidayati, Athi’ (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2025)
This This study aims to examine the concept of spiritual intelligence management according to Hadrotus Syaikh KH Hasyim Asy’ari as outlined in his classical work, Adabul ‘Alim wa al-Muta‘allim. Using a qualitative approach and library research method, this research analyzes the spiritual values and educational ethics promoted by KH Hasyim Asy’ari in shaping the character of both students and educators. Primary data is obtained from the text of Adabul ‘Alim wa al-Muta‘allim, while secondary data is drawn from relevant literature, including biographies, scholarly journals, and other academic works. The findings indicate that spiritual intelligence management from KH Hasyim Asy’ari’s perspective includes managing sincere intentions, developing noble character, showing respect for knowledge and teachers, and maintaining spiritual discipline throughout the teaching and learning process. Core values such as ikhlāṣ (sincerity), tawāḍu‘ (humility), and riyāḍah al-nafs (spiritual self-discipline) serve as the main foundations for nurturing students’ souls to become not only intellectually capable but also spiritually mature. These findings are highly relevant to be applied in contemporary Islamic education as a model for character- and spirituality-based learning.